A Comparative Study of the Multistage Solar Stills with Stacked Stages (MSS-SS) - Mfanafuthi Mthandeni Mkhize; Velaphi Msomi (Journal of Engineering)
The current work conducts a comparative study of the waterbed multistage solar still with stacked stages (MSS-SS) and the vapour-based MSS-SS. Various experimental test results obtained from the vapour-based MSS-SS are briefly discussed in comparison with the waterbed MSS-SS reported in the literature. Based on the experimental observations and tests, the stage tray requires no maintenance and upper stages can operate even when the lower stages are nonoperational. About 0.8–41.3% distillate yield dropped from the upper stages when lower stages were exposed to the atmosphere. The upper stages increased their productivity by 7.1–15.4% when the lower stages were shut off completely. The waterbed-based MSS-SS preserves and reuses thermal energy much better even during off sunshine hours than the vapour-based system. The vapour-based MSS-SS is only productive during sunshine hours, and about 97-98% of the distillate is produced during daytime. Furthermore, the vapour based was able to produce 6.3 kg/day on average on the selected days.